DEVELOPMENT OF COMPLEX PROCESSING TECHNOLOGY FOR THE SECONDARY MASS OF WATERMELONS AND ZUCCHINI - Meliboyev, Mirazam (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
The main stages of the convective drying process, the effectiveness of the method and the possibilities of energy savings of pumpkin polyz products are analyzed. Opinions have also been expressed on the application of the technology in production conditions, its advantages and disadvantages. Detailed information will be given about the role and importance of this technology in the long-term preservation and quality preservation of zucchini. The article is aimed at contributing to the development of the agrarian industry and looking for ways to improve energy efficiency.